1978
DOI: 10.1007/bf02774914
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular transplantation

Abstract: Hepatocellular transplantation into the spleen was investigated as a new attempt in utilizing isolated hepatocytes to compensate for impaired liver function. Present study was undertaken to evaluate morphological and histochemical alterations up to 6 weeks following transplantation in hepatocytes transplanted into the splenic parenchyma. Light microscopic studies revealed viable hepatocellular islets in the splenic parenchyma up to 6 weeks, although minimal cytoplasmic changes were observed. Electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Unfortunately, there is little information from large animal studies to indicate whether intrasplenic engraftment of hepatocytes after infusion through the splenic artery will be adequate. 34 In these experiments, the transplanted cells significantly prolonged animal survival but appeared to lose function over time. The factors contributing to this relatively transient improvement in liver function are unclear.…”
Section: Discussionmentioning
confidence: 82%
“…Unfortunately, there is little information from large animal studies to indicate whether intrasplenic engraftment of hepatocytes after infusion through the splenic artery will be adequate. 34 In these experiments, the transplanted cells significantly prolonged animal survival but appeared to lose function over time. The factors contributing to this relatively transient improvement in liver function are unclear.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, in arterial circulations, e.g., pulmonary and mesenteric beds, greater shear stress or other factors lead to rapid fragmentation of transplanted hepatocytes. 5,20 Previous estimates indicated that less than 20% of the transplanted hepatocytes survive long term in the liver. 8,21 Our data here show that transplanted cells are lost fairly early, as less than 30% of the hepatocytes were found in the liver at 24 hours after transplantation compared with at 2 hours after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…After hepatocyte transplantation, recipient animals were killed at 2, 4,6,8,12,16,20, and 24 hours, and at 2, 3, 4, and 7 days for tissue analysis. These animals received 2 ϫ 10 7 hepatocytes via the spleen.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, transplanted hepatocytes do not survive in arterial circulations, including the hepatic and pulmonary arterial beds, which expose hepatocytes to shear stress. 30,31 Large numbers of hepatocytes may not survive even in low-pressure vascular beds, e.g., the portal bed, where 80% of the transplanted hepatocytes are destroyed within 24 to 48 hours. 4,23,32 Only cells translocating into liver plates survive in the long term.…”
Section: Discussionmentioning
confidence: 99%